Pelaku UMKM di Kota Malang taat pajak? - Metana Hemas En Ardhabilly; Norman Duma Sitinjak (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2020)
Research on tax compliance is always important because the role of tax for the government is very large. MSME also contributes to the stability of the Indonesian economy and includes those who have tax obligations. This study examines the compliance of MSME tax payers in Malang. The findings in this study are tax awareness affects tax compliance. Keyword: knowledge, awareness, tax compliance, MSME